Dietary supplementation with Mexican foods, Opuntia ficus indica, Theobroma cacao, and Acheta domesticus: Improving obesogenic and microbiota features in obese mice - Rosas-Campos, Rebeca; Meza-Rios, Alejandra; Rodriguez-Sanabria, J. Samael; Rosa-Bibiano, Ricardo De la; Corona-Cervantes, Karina; García-Mena, Jaime; Santos, Arturo; Sandoval-Rodriguez, Ana; Armendariz-Borunda, Juan (Frontiers in Nutrition, 2022)
Introduction An obesogenic diet, a diet high in saturated fats and sugars, is a risk factor for the development of multiple obesity-related diseases. In this study, our aim was to evaluate the effect of supplementation with a mixture of Mexican functional foods (MexMix), Opuntia ficus indica (nopal), Theobroma cacao, and Acheta domesticus (edible crickets), compared with a high-fat and fructose/sucrose diet on an obesogenic mice model. Methods For this study, 18 male C57BL/6J mice were used, which were divided into three groups: (1) control group: normal diet (ND), (2) HF/FS group: high-fat diet along with 4.2% fructose/sucrose and water (ad libitum access), and (3) therapeutic group (MexMix): HF/FS diet up to week 8, followed by HF/FS diet supplemented with 10% nopal, 10% cocoa, and 10% cricket for 8 weeks. Results MexMix mice showed significantly reduced body weight, liver weight, visceral fat, and epididymal fat compared with HF/FS mice. Levels of triglycerides, cholesterol, LDL cholesterol, insulin, glucose, GIP, leptin, PAI-1, and resistin were also significantly reduced. For identifying the gut microbiota in the model, 16S rRNA gene sequencing analysis was performed, and the results showed that MexMix supplementation increased the abundance of Lachnospira, Eubacterium coprostanoligenes, and Blautia, bacteria involved in multiple beneficial metabolic effects. It is noteworthy that the mice supplemented with MexMix showed improvements in cognitive parameters, as evaluated by the novel object recognition test. Conclusion Hence, supplementation with MexMix food might represent a potential strategy for the treatment of obesity and other diseases associated with excessive intake of fats and sugars.